Rationalizing the Influence of Tunable Energy Levels on Quantum Efficiency to Design Optimal Non‐Fullerene Acceptor‐Based Ternary Organic Solar Cells. Issue 16 (9th March 2023) - Karuthedath, Safakath; Paleti, Sri H. K.; Sharma, Anirudh; Yin, Hang; P. De Castro, Catherine S.; Chen, Si; Xu, Han; Alshehri, Nisreen; Ramos, Nicolas; Khan, Jafar I.; Martin, Jaime; Li, Gang; et al.
Abstract: Non‐fullerene acceptor (NFA)‐based ternary bulk heterojunction solar cells (TSC) are the most efficient organic solar cells (OSCs) today due to their broader absorption and quantum efficiencies (QE) often surpassing those of corresponding binary blends. The impact on QE of the energetics driving charge transfer at the electron donor:electron acceptor (D/A) interfaces is studied in blends of PBDB‐T‐2F donor with several pairs of lower bandgap NFAs. As in binary blends, the ionization energy offset between donor and acceptor (ΔIE) controls the QE and maximizes for ΔIE > 0.5 eV. However, ΔIE is not controlled by the individual NFAs IEs but by their average, weighted for their blending ratio. Using this property, the QE of a PBDB‐T‐2F:IEICO binary blend that has an insufficient ΔIE for charge generation is improved by adding a deep IE third component: IT‐4F. Combining two NFAs enables to optimize the D/A energy alignment and cells' QE without molecular engineering. Abstract : Similar to binary organic solar cells, ternary cells' quantum efficiency (QE) is controlled by the D/A ionization energy offset (ΔIE) required to overcome the interfacial energy levels bending. Hole transfer occurs though a single channel controlled by the average of ΔIE, weighted for the acceptors ratios. This ratio can thus be adjusted to optimize QE and energy losses.